Mycophenolic Acid for Topical Immunosuppression in Vascularized Composite Allotransplantation: Optimizing Formulation and Preliminary Evaluation of Bioavailability and Pharmacokinetics - Feturi, Firuz G.; Weinstock, Matthias; Zhao, Wenchen; Zhang, Wei; Schnider, Jonas T.; Erbas, Vasil E.; Oksuz, Sinan; Plock, Jan A.; Rohan, Lisa; Spiess, Alexander M.; Ferreira, Lydia M.; Solari, Mario G.; et al. (Frontiers in Surgery, 2018)
ABSTRACT Aim: Mycophenolic acid (MPA), the active form of the ester prodrug mycophenolate mofetil (MMF), is an FDA approved immunosuppressive drug that has been successfully used in combination systemic therapy with other immunosuppressive drugs for the prevention of acute rejection (AR) following solid organ transplantation (SOT) and vascularized composite allotransplantation (VCA). Systemic use of MPA, however, is associated with gastrointestinal adverse effects. Topical delivery of MPA in VCA could provide graft-targeted immunosuppression with minimal systemic drug exposure and side effects. Our goal was to prepare a topical formulation of MPA with optimal in vitro / in vivo characteristics such as release, permeation, and tissue bioavailability in preparation for safety and efficacy evaluation in VCA. Materials and Methods: Permeation studies were performed with a solution of MPA (10mg/ml). In vitro release and permeation studies were performed for different semisolid formulations (aladerm, lipoderm, emollient, and versa- base) of MPA (1%w/w) using a Franz diffusion cells. In vivo pharmacokinetic characterization of MPA released from lipoderm was performed in rats. Results: MPA in solution exhibited a steady state flux (3.8±0.1 µg/cm2/hr) and permeability (1.1x10-7± 3.2x10-9 cm/s). MPA in lipoderm exhibited a steady state flux of 1.12±0.24 µg/cm2/hr, and permeability of 6.2 x10-09 ±1.3 x10-9 cm/s across the biomimetic membrane. The cumulative release of MPA from lipoderm, showed a linear profile over time with a R2 of 0.969. In vivo studies with MPA in lipoderm showed markedly higher local tissue MPA concentrations but lower systemic MPA exposure as compared to parenteral delivery of the same dose of MPA (p<0.05). Conclusion: We have developed a topical formulation of MPA and demonstrated its in vitro/in vivo permeability characteristics. MPA in lipoderm was identified as the optimal topical formulation with high local exposure but low systemic exposure in vivo. Our study lays the groundwork for future efficacy studies in animal models and for novel topical application of immunosuppressive agent in clinical VCA.